Platelet function of whole blood after short‐term cold storage: A prospective in vitro observational study - Kusudo, Eriko; Murata, Yutaka; Matsumoto, Tsuguhiro; Kawamoto, Shuji; Egi, Moritoki (Transfusion (Philadelphia, Pa.), 2023)
Background There is no standardized storage temperature of whole blood for acute normovolemic hemodilution (ANH). Study Design and Methods We conducted a prospective observational study to examine the difference in platelet function between short‐term whole blood storage at 4 and 22°C. Venous blood (40 ml) was collected from seven healthy subjects who gave prior written consent. The samples were divided into three groups: before storage (group Pre), cold (4°C) storage (group C), and room temperature (22°C) storage (group R). Groups C and R were tested after 6 h of blood storage. Platelet aggregability, platelet factor 4 (PF4), β‐thromboglobulin (β‐TG), P‐selectin expression, pH, PO2, PCO2, glucose, lactate, blood count, and thromboelastography (TEG) parameters were measured. The percentage change in each parameter in groups C and R was calculated using the value in group Pre as a reference. These data were then compared between groups C and R using a Wilcoxon matched pairs test. p < 0.05 was considered to be statistically significant. Results Compared with group R, group C showed significantly higher platelet aggregability with adenosine diphosphate (ADP) 2, 4, and 6 μM (all p = 0.016) and collagen 1 μg/ml (p = 0.047) stimulation, and significantly lower PF4 and β‐TG elevation (both p = 0.031), glucose consumption (p = 0.031), and lactate production (p = 0.016). The ADP channel in TEG showed a significant increase in platelet aggregation rate in group C compared to group R. Discussion Cold storage of whole blood in ANH may provide improved storage conditions for platelets and contribute to improved hemostasis compared to room temperature storage.